Rickettsia Deregulates Genes Coding for the Neurotoxic Cell Response Pathways in Cerebrocortical Neurons In Vitro - Martin Cente; Monika Danchenko; Ludovit Skultety; Peter Filipcik; Zuzana Sekeyova (Cells, 2023)
Rickettsial infections of the central nervous system (CNS) are manifested by severe neurological symptoms and represent a serious life-threatening condition. Despite the considerable health danger, only a few studies have been conducted focusing on the pathogenesis induced by Rickettsia sp. in CNS. To investigate the signaling pathways associated with the neurotoxic effects of rickettsiae, we employed an experimental model of cerebrocortical neurons combined with molecular profiling and comprehensive bioinformatic analysis. The cytopathic effect induced by Rickettsia akari and Rickettsia slovaca was demonstrated by decreased neuronal viability, structural changes in cell morphology, and extensive fragmentation of neurites in vitro. Targeted profiling revealed the deregulation of genes involved in the neuroinflammatory and neurotoxic cell response pathways. Although quantitative analysis showed differences in gene expression response, functional annotation revealed that the biological processes are largely shared between both Rickettsia species. The identified enriched pathways are associated with cytokine signaling, chemotaxis of immune cells, responses to infectious agents, interactions between neurons, endothelial and glial cells, and regulation of neuronal apoptotic processes. The findings of our study provide new insight into the etiopathogenesis of CNS infection and further expand the understanding of molecular signaling associated with neuroinvasive Rickettsia species.